Projeto Digit-M-Ed - Hiperconectando: alunos como formadores no ambiente escolar - Manzati, Guilherme Rittner (2018)
The objective of this research is to investigate if/how students from a state school - located in a city of the Greater São Paulo and participant of the project “Digit-M-Ed – Hiperconectando” comprehend and transform their participation in the school community, as well as which transformations happened in their actions at and towards the school. Therefore, when analyzing how students comprehend the roles of administrators, teachers and their own purpose in the organization of school activities, I analyze if there was a change in the students’ participation in the school life, and - if the change happened indeed - point out which were they. It is also part of this research to analyze which are the goals of the new courses of action, and how students that took part in them organized themselves at school in order to make it possible to execute a new way of acting in an organizational system traditionally consolidated. To that end, I promote a theoretical discussion capable of encompassing a conception of education for freedom according to Santos (2010) Freire (2012), Torres Santomé (2013) and Liberali (2015), I contextualize based on the Social Historical Theory (VYGOTSKY (1930, 1934) and the Social Historical Activity Theory (ENGESTRÖM, 1987, 2001) the guiding aspects of an education able to raise the individual’s awareness about their context and their way of acting, creating space for a planned education supported by other main concepts such as the Creative Chain (LIBERALI, 2009) and Mobility (BLOMMAERT, 2012; 2013; 2014), all important to enable individuals to act in the spaces they occupy. The theoretical-methodological organization of this research is driven by the Critical Collaborative Research - PCCol (MAGALHÃES, 1994; 2009), in which the relations among the participants are characterized as collaborative and critical. For the analysis, I use a semi-structured interview with students from a peripheral State school in São Paulo. The results reveal the development of different types of agencies, i.e., transformative (ENGESTRÖM; SANNINO, 2011), relational (EDWARDS, 2005, 2007, 2011;), critical collaborative (NININ; MAGALHÃES, 2017) and desencapsulated (LIBERALI, 2015) as well as the redefinition of the students’ roles at school, as a result of the Digit-M-Ed participation